2019
DOI: 10.1109/access.2019.2950390
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Energy-Saving Driving Strategy for Electric Buses

Abstract: In recent years, fully electric vehicles (EVs) have accounted for a higher proportion of urban buses. On account of their relatively short cruising range, many technologies were used to improve the driving range, such as improving energy management strategies and promoting the performance of the battery and engine. The purpose of this study was to develop an energy-efficient driving strategy to save energy. The strategy consists of two parts: determining a velocity interval for lower energy and establishing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…In order to build a comprehensive, reasonable, and feasible evaluation index system, it is necessary to consider the operational characteristics of buses. Based on relevant research results, in view of the operational characteristics of buses and the technical characteristics of pure electric buses, the initial application performance index system of pure electric buses is shown in Figure 1 [1,3,9].…”
Section: Construction Of the Initial Index Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to build a comprehensive, reasonable, and feasible evaluation index system, it is necessary to consider the operational characteristics of buses. Based on relevant research results, in view of the operational characteristics of buses and the technical characteristics of pure electric buses, the initial application performance index system of pure electric buses is shown in Figure 1 [1,3,9].…”
Section: Construction Of the Initial Index Systemmentioning
confidence: 99%
“…At present, there are many performance evaluation models for electric buses, mainly focusing on battery performance evaluation and environmental impact evaluation. In terms of battery performance evaluation, since the mileage of pure electric buses is less than that of traditional buses, Zhang et al [1] believe that mileage is the focus of performance evaluation, and the battery energy-saving performance is used as an indicator to build an evaluation model. Jwa et al [2] compared various electric buses with diesel buses and compared their environmental impacts during the life cycle and found that lithium battery electric buses are better in terms of energy consumption and emissions, but there are still problems in terms of travel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some researchers explored the energy-saving strategies with the emerging of new communication technologies buses. Zhang et al built a simulation-based model for energy optimization of electric buses without stopping between two adjacent stops [14]. Hu et al proposed an integrated control strategy with speed guidance and signal priority control on bus lanes [15].…”
Section: Introductionmentioning
confidence: 99%
“…The system main screen consists of several sections to help the driver's driving strategy. Zhang et al suggested that driving strategy refers to the combination of acceleration mode and velocity values chosen by the driver to traverse a given distance [40]. Thus, the main screen composed of four sections: navigation route, traffic information on the route, lane information, and other important information, such as personal schedule.…”
mentioning
confidence: 99%